2003
DOI: 10.1177/073401680302800102
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Causal Attribution on Correctional Ideology: A National Study

Abstract: There is a long-standing argument that how people think about punishment is tied directly to their beliefs about why people engage in criminal behavior. Support for a relationship between causal attribution and punitiveness has been found in the literature, with key differences discerned between those who attribute crime to individual characteristics of offenders and those who view crime as a result of structural characteristics. This article broadens the scope of earlier studies through the development and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 25 publications
3
58
0
Order By: Relevance
“…"Those who hold a classical understanding of crime causation and hence believe that crime flourishes because it is a rational, utilitarian enterprise will be more punitive than those positivists … who see crime as a manifestation of social constraint and social ills" (Cullen et al 1985: 310) This correlation has been confirmed in both quantitative and qualitative studies of public opinion with samples ranging from university students to probation officers and judges to nationally representative public samples (e.g., Carroll et al 1987;Grasmick and McGill 1994;Sasson 1995;Sims 2003;Templeton and Hartnagel 2008; but see Viney et al 1982). Scheingold (1984) argues that "hard-line" conservatives view offenders as free individuals who choose to prey on others, whereas liberals are "positivists" who argue that "crime is associated with poverty… weakened family structures, inadequate slum schools, limited job opportunities, and the like" (p. 9).…”
mentioning
confidence: 82%
“…"Those who hold a classical understanding of crime causation and hence believe that crime flourishes because it is a rational, utilitarian enterprise will be more punitive than those positivists … who see crime as a manifestation of social constraint and social ills" (Cullen et al 1985: 310) This correlation has been confirmed in both quantitative and qualitative studies of public opinion with samples ranging from university students to probation officers and judges to nationally representative public samples (e.g., Carroll et al 1987;Grasmick and McGill 1994;Sasson 1995;Sims 2003;Templeton and Hartnagel 2008; but see Viney et al 1982). Scheingold (1984) argues that "hard-line" conservatives view offenders as free individuals who choose to prey on others, whereas liberals are "positivists" who argue that "crime is associated with poverty… weakened family structures, inadequate slum schools, limited job opportunities, and the like" (p. 9).…”
mentioning
confidence: 82%
“…How people understand the causes of crime influences the policies they support to fight crime (Carroll, Perkowitz, Lurigio, & Weaver, 1987;Cullen et al, 1985;Hawkins, 1981;Sims, 2003). Those who hold a "classical" view and believe criminal behavior is the result of individual failings should prefer harsh punishments for criminal offenders.…”
Section: The Racial Gap In Punitivenessmentioning
confidence: 98%
“…Such inferences are beliefs that allow for the understanding and prediction of the observable world (Rifon et al, 2004). Heider (1958) outlined the types of factors that can form the attribution of a motive: (1) internal/dispositional properties that endorse personal responsibility (intrinsic motives ;Heider, 1958;Sabini, Siepmann, & Stein, 2001;Sims, 2003;Skitka, Mullen, Griffin, Hutchinson, & Chamberlin, 2002) and (2) external/situational properties that consider environmental influences as a causal factor (extrinsic motives; Cullen, Clark, Cullen, & Mathers, 1985;Heider, 1958;Sims, 2003;Woolfolk, Doris, & Darley, 2006). Although individuals may make both internal and external attributions to explain some conduct (Funder, 2001;Unnever, Cochran, Cullen, & Applegate, 2010) when asked to make decisions about the cause of some behavior, they tend to prefer one attribution style over another (Heider, 1958;Reeder, Vonk, Ronk, Ham, & Lawrence, 2004).…”
Section: Attribution Theorymentioning
confidence: 99%